Gambaran Radiografi Toraks Sebagai Prediktor Outcome Pasien COVID-19 - Safarini, Bekti; Sutikno, Dria Anggraeny; Intisari, Dewi (Jurnal Kesehatan Andalas, 2024)
COVID-19 (coronavirus disease 2019) is a pulmonary infection disease caused by SARS-CoV-2. Chest radiographic examination of COVID-19 cases performed to make a diagnosis and monitor therapy. Objective: To    evaluated the results of chest radiography examination in COVID-19 cases as a predictor of patient outcome after treatment at the Sultan Agung Islamic Hospital in Semarang. Methods: This research was an observational analytic study with a retrospective design using medical record data from January until December 2021. The results of chest radiographs were analyzed using the Brixia Score system with a maximum score of 18. Outcomes of COVID-19 patients were described as recovered patients or died. Data analysis uses the ROC curve to determine the cut-off point. Results: This study showed that out of 47 patients (43±14 years old), 39 patients (81%) recovered and nine patients died (19%). The levels of leukocytes, D-dimer, Neutrophil-lymphocyte ratio (NLR), and Brixia scores were significantly higher in dead patients (p<0.05). Sensitivity and specificity values predictor of leukocyte count (83%, 61%), D-dimer (83%, 84%), NLR (83%, 82%), and Brixia score (83%, 79%), respectively. Conclusion: Increased levels of leukocytes, D-dimer, NLR, and Brixia Score can be used as a predictor of patient mortality after hospitalization.Keywords: Brixia score, COVID-19, thoracic radiograph